STRATÉGIES TRANSNATIONALES DANS L’ŒUVRE DE MIRCEA ELIADE - ILEA, Laura T. (Studia Universitatis Babeș-Bolyai Philologia, 2021)
Transnational Strategies in Mircea Eliade’s Writings. In this article, we will consider the techniques through which an important hallmark of Romanian culture, Mircea Eliade, negotiated his transnational strategies, in a continual back-and-forth movement between his place of origin and a larger, cosmopolitan context. Paradoxically, as proven by Paul Cernat, it is not exoticism that will lead to his treatises on the history of religions, but on the contrary, the return to Sambo’s room, as described in The Forbidden Forest novel. Moreover, the European modernist project, defended by Eliade, is in itself an antinomic project: exceptional avant-garde techniques succeed regressive strategies. The latter are based on the modern hermeneutics of meaning, developed by Eliade in his approach to the history of religions, which is an all-encompassing way of interpreting religious facts as hierophanies. REZUMAT. Strategii transnaționale în opera lui Mircea Eliade. În acest articol, vom analiza tehnicile prin care un reper important al culturii române, Mircea Eliade, și-a negociat strategiile transnaționale, într-o continuă mișcare între locul de origine și un context mai larg, cosmopolit. În mod paradoxal, așa cum o demonstrează Paul Cernat, nu exotismul este cel care va conduce înspre tratatele de istoria religiei ci, dimpotrivă, reîntoarcerea la camera Sambo, așa cum e ea descrisă în romanul Noaptea de Sânziene. Mai mult, proiectul modernist susținut de Eliade este în sine un proiect antinomic : tehnici avangardiste de excepție succedă unor strategii regresive. Acestea din urmă sunt bazate pe hermeneutici moderne ale sensului, dezvoltate de Eliade în abordarea istoriei religiilor, care reprezintă un mod extins de interpretare a faptelor istorice ca hierofanii. Cuvinte-cheie: teroarea istoriei, strategii antimoderniste, hierofanie, autohtonism, tehnici transnaționale